Effects of Climate Change on Malaria Risk to Human Health: A Review - Dereba Muleta Megersa; Xiao-San Luo (Atmosphere)
Malaria, a severe vector-borne disease, affects billions of people globally and claims over half a million lives annually. Climate change can impact lifespan and the development of vectors. There is a gap in organized, multidisciplined research on climate change’s impact on malaria incidence and transmission. This review assesses and summarizes research on the effects of change in climate on human health, specifically on malaria. Results suggest that higher temperatures accelerate larval development, promote reproduction, enhance blood feed frequency, increase digestion, shorten vector life cycles, and lower mortality rates. Rainfall provides aquatic stages, extends mosquitoes’ lifespans, and increases cases. Mosquito activity increases with high humidity, which facilitates malaria transmission. Flooding can lead to increased inhabitation development, vector population growth, and habitat diversion, increasing breeding sites and the number of cases. Droughts can increase vector range by creating new breeding grounds. Strong storms wash Anopheles’ eggs and reproduction habitat. It limits reproduction and affects disease outbreaks. The Indian Ocean Dipole (IOD) and El Nino Southern Oscillation (ENSO) indirectly alter malaria transmission. The study recommends strengthening collaboration between policymakers, researchers, and stakeholders to reduce malaria risks. It also suggests strengthening control mechanisms and improved early warnings.